2014
DOI: 10.1111/ajd.12194
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of cutaneous metastases at the National Skin Centre Singapore

Abstract: Cutaneous metastases are highly variable in presentation and a high index of suspicion is required for prompt diagnosis, especially in patients with a history of cancer, regardless of stage of treatment of the primary tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 24 publications
8
31
0
8
Order By: Relevance
“…Cutaneous metastases occur in approximately 0.7–10% of patients with invasive carcinomas. Although uncommon, and comprising approximately 2% of all skin tumours, when present they usually predict a poor prognosis [5] . These skin manifestations are usually seen in patients with advanced disease, but they can be the presenting sign of a neoplastic disorder in 12% of the patients [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cutaneous metastases occur in approximately 0.7–10% of patients with invasive carcinomas. Although uncommon, and comprising approximately 2% of all skin tumours, when present they usually predict a poor prognosis [5] . These skin manifestations are usually seen in patients with advanced disease, but they can be the presenting sign of a neoplastic disorder in 12% of the patients [7] .…”
Section: Discussionmentioning
confidence: 99%
“…With an aging population and increases in the average life expectancy and the incidence of cancer, the global burden of cancer is expected to grow. It is therefore important for clinicians and pathologists to be aware of the clinical spectrum of cutaneous metastases, and to have a high index of suspicion for early diagnosis and prompt management [5,7] . Gan et al reported that in a cohort of 35 patients with confirmed cutaneous metastases, the diagnosis was suspected in 72% (n=25), based on clinical features (46%, n=16) or the presence of active metastatic disease elsewhere (26%, n=9) [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La mayoría de las MC se pueden presentar como nódulos de rápido crecimiento, aunque pueden presentarse también como pápulas, placas o lesiones ulceradas (3,4) . El tipo histológico más frecuente es el adenocarcinoma.…”
Section: Introductionunclassified
“…El tipo histológico más frecuente es el adenocarcinoma. En el estudio histopatológico se observan acúmulos de las células en la dermis sin contacto con la epidermis subyacente (3,4) .…”
Section: Introductionunclassified